The Usefulness of Instagram Posts Tagging Hand Surgery Conditions - Zhang, Dafang; Earp, Brandon E. (Journal of Hand and Microsurgery, 2020)
Introduction The objective of this study was to assess the usefulness of Instagram posts for users seeking information about common hand conditions.Materials and Methods An internet-based study was performed of the top 200 trending posts on Instagram for each of the tags #carpaltunnel and #triggerfinger. The trending position (1 through 200), number of likes (for all posts), and number of views (for video posts only) were recorded. Each post was assessed to determine whether it would be useful for a user seeking medical information. Useful and not useful posts were further classified into thematic categories.Results Useful posts comprised only 21% of #carpaltunnel posts and 12% of #triggerfinger posts. #carpaltunnel had a significantly higher proportion of useful posts than #triggerfinger. For both #carpaltunnel and #trigger finger, useful posts were not associated with trending position or number of likes. Useful posts commonly provided a clinical image or an anatomical diagram. Posts that were not useful were generally irrelevant to the hand condition, but a minority provided information not supported by evidence or were solely advertising material.Conclusion Hand surgery patients can be educated that, in its current form, Instagram is not a source of useful information about common hand conditions.
Keywords: health literacy; Instagram; information; internet; online; quality; social media